DESIGN, ANALYSIS AND OPTIMIZATION OF BRAKE DISC MADE OF COMPOSITE MATERIAL FOR A MOTOR CYCLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The most important component in vehicle is suspension system which directly affects the safety performance and noise level. Suspension arm is one of the most important components in the suspension system. It is fitted in various types of the suspensions like Macpherson wishbone or double wishbone suspensions. The lower control arm is a wishboneshaped metal strut that attaches the wheel to the vehicles frame. In order to determine the deformation and stress distribution in the current design the finite element analysis is carried out. The baseline model of the lower control arm is created by using solid modeling software viz. CATIA. ANSYS Workbench is used for Finite Element Analysis This study deals with Finite Element Analysis of the Lower control arm of Mac pherson suspension system.